(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This paper explores the development and application of on-demand disaster recovery strategies to ensure organizational continuity amidst crises. Through a combination of case studies and qualitative analysis, we investigate various real-world applications of instant recovery solutions across diverse scenarios, including natural disasters, technological disruptions, and security breaches. The findings highlight the adaptability and efficiency of on-demand mechanisms in minimizing operational downtime and mitigating financial losses. The research underscores the need for robust, flexible disaster recovery plans that integrate technology and preparedness to swiftly respond to emergencies. This study contributes to the evolving field of disaster management by providing actionable insights and a framework for organizations seeking to enhance their resilience against unforeseen disasters